Disease course and viral shedding in experimental Norwalk virus and Snow Mountain virus infection - Kirby, A.E.; Shi, J.; Montes, J.; Lichtenstein, M.; Moe, C.L. (Journal of medical virology, 2014)
Norovirus is the most common cause of acute infectious gastroenteritis, causing approximately 21 million cases annually in the USA. The virus is highly contagious and resistant to decontamination, making outbreaks difficult to control. To facilitate the development of better control methods, this study characterized the viral shedding patterns in stools from subjects experimentally infected with genogroup I or II norovirus. Viral stool titers were determined by quantitative real‐time RT‐PCR for all stools produced in the first 7 days post‐challenge and representative stools through day 35 post‐challenge. The shedding titers and disease course were analyzed with respect to virus type, illness, and subject demographics. Infection with GII.2 Snow Mountain (SMV) resulted in more symptoms and a higher frequency of painful symptoms compared to GI.1 Norwalk (NV) infection. However, NV infection produced stool viral titers approximately 2 logs higher than those seen in SMV infections. Both NV and SMV were shed in stools for up to 3 weeks after the resolution of symptoms, but long shedding durations were more common in NV infections. For each challenge virus, shedding titers and patterns were not correlated with subject demographics or clinical course. This is the first study to report shedding dynamics in experimental GII norovirus infection. J. Med. Virol. 86:2055–2064, 2014. © 2014 Wiley Periodicals, Inc.